DEED OF SALE AND PURCHASE IN PRUDENTIAL PRINCIPLE APPLICATION BASED ON AN ABSOLUTE POWER OF ATTORNEY (STUDY DECISION NUMBER: 2255 K/PDT/2014) - GINA FELISSIMO HALEVI; TRI LISIANI PRIHATINAH; RIRIS ARDHANARISWARI (Authentica, 2023)
The displacement of land rights through sale and purchase is required to be carried out before the PPAT either directly by the parties or by the attorney given power, the party which has been given the power of attorney by the land owner (seller) or by the buyer with a power of attorney to sell, made before a Notary, however, power of attorney for selling can be the basis for buying and selling land as stated in the Instruction of the Minister of Home Affairs Number 14 of 1982 concerning the Prohibition of Absolute Power of Attorney as a Transfer of Land Rights issued on March 6 1982, to that, a Notary /PPAT must take an attentive action in the land sales process, despite the fact that the Notary/PPAT does not fully implement the principle of prudence, in addition, the legal validity of the Deed made is questionable. The formulation in this research is: (1) What is the validity of the use of an absolute power of attorney made by a notary in making a land sale and purchase deed? (2) How is the Precautionary Principle applied to the Preparation of Sale-Purchase Deeds by PPAT? This research was conducted using a normative juridical method with a statutory approach and a conceptual approach. The research specification used is an analytical perspective, such as describing and analyzing facts through a statutory approach. The source of legal materials use library research data techniques based on research results. Notaries/PPATs in carrying out their duties and authority must always use the principle of prudence and either PPAT in making authentic deeds should be based on absolute power of attorney and the validity of the power of attorney, in which PPAT should have rejected from the start because absolute power of attorney is prohibited in the land buying and selling process.Keywords: Precautionary principle; Notary/PPAT; Absolute power of attorney.